(3dHGH GdeMUd aj CUhd GdOjfs - (3YHO GdQMef Hf eMeO Hf NdOhf GdMVQeis; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3CMeO ef JaQO HYXeJg hcHQjGFg , hJbOS HUaGJg hCSeGFg Edi Cf WdY GdBf HSeGFg CHh YHO Gddg eMeO Hf EHQGgje GdCHdi s
(3BNQgG (B:s
(3hbO hVY GFeI GdQGaVI dJTjYge ebGdJjf eeG jXgQ Ydjge hdfNJe GdcJGH MGeOjf Gddg heUdjf Ydi eMeO fHjg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3CUhd Gdabgs